The patient, data protection and changing healthcare models : the iImpact of e-health on informed consent, anonymisation and purpose limitation - Verhenneman, Griet (Cambridge : Intersentia, 2021)
Healthcare is changing. It is moving to a paperless environment and becoming a team-based, interdisciplinary and patient-centred profession. Modern healthcare models reflect our data-driven economy, and adopt value-driven strategies, evidence-based medicine, new technology, decision support and automated decision-making. Amidst these changes are the patients, and their right to data protection, privacy and autonomy. The question arises of how to match phenomena that characterise the predominant ethos in modern healthcare systems, such as e-health and personalised medicine, to patient autonomy and data protection laws. That matching exercise is essential. The successful adoption of ICT in healthcare depends, at least partly, on how the public's concerns about data protection and confidentiality are addressed. Three backbone principles of European data protection law are considered to be bottlenecks for the implementation of modern healthcare systems: informed consent, anonymisation and purpose limitation. This book assesses the adequacy of these principles and considers them in the context of technological and societal evolutions. A must-read for every professional active in the field of data protection law, health law, policy development or IT-driven innovation. GRIET VERHENNEMAN is a legal expert on e-health with an academic background. Today Griet is Data Protection Officer at the University Hospitals KU Leuven (UZ Leuven). Previously, she worked as a legal researcher at the Centre for IT and IP Law KU Leuven (CiTiP) and participated in several interdisciplinary projects. Griet continues her collaboration with the Centre as a Research Fellow. In her position of Data Protection Officer, Griet brings data protection into practice. Through her work as an academic, Griet continues to assess, discuss and disseminate about the legal implications of ICT-driven evolutions in the field of health and medicine.
Title from publisher's bibliographic system (viewed on 28 May 2021).
Keywords: Medical care -- Data processing; Data protection